Chronic painless stanford type a aortic dissection involving whole of the aorta in an elderly female - Kunal Mahajan (Journal of the Practice of Cardiovascular Sciences, 2019)
Stanford type A aortic dissection (AD) is a rapidly progressive disease associated with a very high mortality rate, especially in the absence of emergent surgical repair. However, very rarely, few cases remain undiagnosed in acute phase because of atypical or absent symptoms. We present such an atypical case of a chronic painless type A AD in an elderly female, who is still surviving at 6 months follow-up without any surgical/catheter-based intervention. This case emphasizes that chronic type A ADs have different natural history and could potentially be managed differently from the acute lesions.